2020
DOI: 10.1016/j.gloenvcha.2020.102185
|View full text |Cite
|
Sign up to set email alerts
|

Testing smarter control and feedback with users: Time, temperature and space in household heating preferences and practices in a Living Laboratory

Abstract: Testing smarter control and feedback with users: time, temperature and space in household heating preferences and practices in a Living Laboratory. Global Environmental Change, 65. a102185.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The most notable difference was more upper quartile and outlier temperatures in the ZP dwellings which indicate regular use of on-demand heating when desired, potentially leading to more energy use. Borrowing from Sovacool et al 28 defined heating behaviours and the monitoring results discussed in the section before, the following findings emerge:…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The most notable difference was more upper quartile and outlier temperatures in the ZP dwellings which indicate regular use of on-demand heating when desired, potentially leading to more energy use. Borrowing from Sovacool et al 28 defined heating behaviours and the monitoring results discussed in the section before, the following findings emerge:…”
Section: Discussionmentioning
confidence: 86%
“…The most notable difference was more upper quartile and outlier temperatures in the ZP dwellings which indicate regular use of on-demand heating when desired, potentially leading to more energy use. Borrowing from Sovacool et al 28 defined heating behaviours and the monitoring results discussed in the section before, the following findings emerge:• ZP1 is considered to be an ‘On-off Switcher’ or ‘Steady and Savvy’ as they varied their set point the least and were able to maintain a household range between 18 and 20°C.• ZP2 is considered either an ‘On-demand Sizzler’ or a ‘Toasty Cruiser’, maintaining set points mostly between 22–24°C with household temperatures around 22–23°C• ZP3 is considered to be a ‘Cool Conserver’ never heating above 20°C; however, it is not known whether their motivation was due to concern for energy costs.• NZP1 and NZP3 are considered ‘Steady and Savvy’ as they generally maintain temperatures between 18–20°C in the living rooms; however, their bedroom temperature changes may qualify as a different category; generally cooler preferences in NZP3.• NZP2 is considered an ‘On-demand Sizzler’ with a tight temperature range around 23°C though it appears they prefer to sleep much cooler than they keep their living room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies concluded that it took time and effort to configure the SHT, and, because of this, some participants deliberately used the simple features of the smart systems only [ 16 ]. A living-lab longitudinal study of a large number of households ( n = 100) with smart heat control found that preferences for temperature settings, energy savings, and time spent on controlling the technology varied [ 17 ]. Learning processes were discussed in relation to householders’ knowledge, or lack of knowledge, about how much energy or money could be saved from heating less.…”
Section: Introductionmentioning
confidence: 99%